Digitalisasi UMKM di Kelurahan Selapajang Jaya: Strategi Social Media Marketing Dalam Menyongsong Era Modern - Latif, Inas Sofia; Latuconsina, Hudaya; Lesmana, Sri Jaya (Penerbit Goodwood, 2024)
Purpose: The specific goal of this service activity is to help MSMEs in Selapajang Jaya Village strengthen marketing strategies through digital marketing to increase competitiveness. Research methodology: This service method was carried out with Participatory Action Research (PAR) conducted by the UNIS Ramadhan 2023 KKK team. Activities are implemented through socialization and direct assistance to the community. Results: The result of the activity is solving partner problems that are solved through the transfer of science and technology in the form of socialization and assistance related to digital marketing through social media platforms, such as WhatsApp Business, Shopee, and Instagram. Limitations: There is limited time, so the implementation of activities is only focused on the needs of business actors and/or MSMEs related to digital marketing through certain social media platforms. Unstable Internet connections and the lack of digital literacy of relatively old business actors are also challenges in the mentoring process. Contribution: This activity provides additional understanding and increases skills in mastering the steps of business actors and/or MSMEs in RW 005 Selapajang Jaya Village in utilizing social media effectively to optimize online presence and increase visibility and sales of products or services.